2007
DOI: 10.1002/dvdy.21048
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of genetic networks during initiation of the Fetal Alcohol Syndrome

Abstract: Fetal Alcohol Spectrum Disorders (FASD) are birth defects that result from maternal alcohol use. We used a non a priori approach to prioritize candidate pathways during alcohol-induced teratogenicity in early mouse embryos. Two C57BL/6 substrains (B6J, B6N) served as the basis for study. Dosing pregnant dams with alcohol (2؋ 2.9 g/kg ethanol spaced 4 hr on day 8) induced FASD in B6J at a higher incidence than B6N embryos. Counter-exposure to PK11195 (4 mg/kg) significantly protected B6J embryos but slightly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
126
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 102 publications
11
126
4
Order By: Relevance
“…Our findings also corroborate reports that some toxic agents that can cause birth defects have the same or similar effects on the transcriptome (Nemeth et al 2005. The meta-study approaches also support reports of additional condition-dependent effects of teratogenic agents with gene expression patterns highly dependent on the treatment levels compared, including toxic factor, dose, sampling time, and strain (Green et al 2007). …”
Section: Representation Of Genes and Gene Familiessupporting
confidence: 89%
See 4 more Smart Citations
“…Our findings also corroborate reports that some toxic agents that can cause birth defects have the same or similar effects on the transcriptome (Nemeth et al 2005. The meta-study approaches also support reports of additional condition-dependent effects of teratogenic agents with gene expression patterns highly dependent on the treatment levels compared, including toxic factor, dose, sampling time, and strain (Green et al 2007). …”
Section: Representation Of Genes and Gene Familiessupporting
confidence: 89%
“…Maunoury et al (1992) described the association between the regulation of villin gene activity during mouse embryogenesis and the tissue-specific expression observed in adults. Villin is responsible for establishing and maintaining the apical/basal membrane polarity and Green et al (2007) reported differential expression of cytoskeleton genes in the presence of alcohol and the present meta-analysis confirmed this finding. Lee et al (1997) reported dependency of tropomyosin transcripts on alcohol.…”
Section: Representation Of Genes and Gene Familiessupporting
confidence: 85%
See 3 more Smart Citations